1986
DOI: 10.1007/bf00219199
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemistry of GABA in the antennal lobes of the sphinx moth Manduca sexta

Abstract: We have prepared and characterized specific rabbit antisera against gamma-aminobutyric acid (GABA) coupled covalently to bovine serum albumin and keyhole-limpet hemocyanin. Using these antisera in immunocytochemical staining procedures, we have probed the antennal lobes and their afferent and efferent fiber tracts in the sphinx moth Manduca sexta for GABA-like immunoreactivity in order to map putatively GABAergic central neurons in the central antennal-sensory pathway. About 30% of the neuronal somata in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
162
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(176 citation statements)
references
References 17 publications
12
162
1
1
Order By: Relevance
“…Both antisera were raised against conjugates of GABA covalently coupled to hemocyanin. The specificity of the rabbit GABA antiserum for M. sexta tissue has been shown in detail earlier (Hoskins et al, 1986). To demonstrate the specificity of the GABA antiserum raised in guinea pig, we performed double labeling experiments on 40 lm vibrating microtome sections with both anti-GABA antisera.…”
Section: Immunocytochemistrymentioning
confidence: 89%
See 2 more Smart Citations
“…Both antisera were raised against conjugates of GABA covalently coupled to hemocyanin. The specificity of the rabbit GABA antiserum for M. sexta tissue has been shown in detail earlier (Hoskins et al, 1986). To demonstrate the specificity of the GABA antiserum raised in guinea pig, we performed double labeling experiments on 40 lm vibrating microtome sections with both anti-GABA antisera.…”
Section: Immunocytochemistrymentioning
confidence: 89%
“…In M. sexta most of the GABA-ir neurons are LNs, while a small subpopulation belongs to the group of PNs (Hoskins et al, 1986;Homberg et al, 1989). Double labeling with Mas-AT and GABA antisera revealed that in the pupa and in the adult only one Mas-AT-ir type, the LATn, displays additional GABA immunoreactivity.…”
Section: Colocalization Of Mas-at With Gaba Rfamides and A-type Allmentioning
confidence: 96%
See 1 more Smart Citation
“…Historically, LNs have been regarded mostly as GABAergic, inhibitory neurons, and GABAergic LNs have been reported in the AL of various insect species including A. mellifera (Schäfer and Bicker, 1986), Bombyx mori (Iwano and Kanzaki, 2005;Seki and Kanzaki, 2008), D. melanogaster (Wilson and Laurent, 2005), M. sexta (Hoskins et al, 1986), P. americana (Distler, 1989), and S. americana (Leitch and Laurent, 1996). Immunohistochemical, mass-spectrometric and physiological studies, however, showed that the LNs are biochemically a more heterogeneous population of neurons than previously thought.…”
Section: Types Of Local Interneuronsmentioning
confidence: 99%
“…Based on early immunohistochemical (Hoskins et al, 1986;Distler, 1989) and electrophysiological work (Waldrop et al, 1987;Christensen et al, 1993), LNs have historically been regarded as mostly GABAergic and inhibitory. In subsequent studies, GABAergic LNs have been reported in various insect species (Schäfer and Bicker, 1986;Leitch and Laurent, 1996;Iwano and Kanzaki, 2005;Wilson and Laurent, 2005) and the importance of GABAergic, inhibitory LNs for odor information processing was clearly shown (Stopfer et al, 1997;Sachse and Galizia, 2002;Wilson and Laurent, 2005).…”
Section: Introductionmentioning
confidence: 99%